National and political orientation of Muslim press in Bosnia and Herzegovina during the Austro-Hungarian administration (1906-1914) - Jahić, Adnan (Historical Thought, 2025)
This paper illuminates the main views of the Bosniak political elite of the Austro-Hungarian period on national politics and the national identity of the Bosnian Muslims, Bosniaks, whom regional international relations and internal Bosnian political developments provoked to articulate more concrete views on the issues involved. The author points out the important role of Islam and Islamic culture as the substrate and basis of collective self-identification and socio-political affirmation of Bosniaks at the crossroad of the 19th and 20th century.